Simulation model for effective supply chain management using arena - Hashim, Mohd Nurhanif (2008)
Supply chain management (SCM) is a major component of competitive strategy to enhance organizational productivity and projitability. Supply chain is essentially a series of linked suppliers and customers where evel}' customer is in tllm a supplier to the next downstream organization until a jinished product reaches the ultimate end user. In this scenario, two issues have to be overcome namely shrinkage and the bullwhip effict. Computer simulation model can play an important role to identw' the problematic areas and indicate possible solutions. Simulation modeling can help the manufacturer to establish supply chain peliormance and the manufacturer is able make early strategic decisions. A simulation was developed based on infoJ7l1atioJl fi"Oln a paperbased indust,)'. Shrinkage has been identified to occur at the transportation and assembly process module. The bullwhip effect could be seen to occllr even at primm}' supplier as it tries to adapt to the consumer demand fluctuation. Dynamic process simlllation allows organizations to study their process fi"Oll1 a system perspective, providing better understanding of cause and effect in addition to allowing betterpredictioJl of outcomes.